Topika inwencyjna, czyli tworzywo tematyczne i warstwa argumentacyjna wybranych pism polemicznych Piotra Skargi - Jara, Dorota (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The author of this article made an attempt to analyze the thematic material, as well as argumentative techniques in selected polemical papers by Piotr Skarga. She studied both the external, non-artistic evidence (e.g. the Bible, works of Church Fathers, Vatican Council Decrees) and the internal, artistic ones (i.e. enthymemes, topics, exempla). She demonstrated that the Holy Bible was for the preacher Sigismund III Vasa the greatest authority used for the reinforcement of his own argumentation. It was proved that apart from using factual evidence, Skarga would enrich his works with emotional content. For this purpose, he used mostly amplification, which for the Jesuit was at the same time one of the main tools of persuasion.